2022
DOI: 10.1038/s41523-022-00456-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute health-related quality of life outcomes and systemic inflammatory markers following contemporary breast cancer surgery

Abstract: Contemporary breast cancer surgical procedures vary greatly by the amount of tissue removed, anesthesia time, and reconstruction. Despite historical literature comparing the health-related quality of life (HRQOL) after lumpectomy and mastectomy, HRQOL data are limited regarding contemporary surgical procedures. Further, biological processes (e.g., inflammation) associated with HRQOL outcomes have not been described. We conducted two studies to examine differences in post-operative physical and mental functioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…We found that IL‐6, IL‐10, and TNF‐α had a direct relationship with cognition in survivors and controls, findings that parallel prior work by others 13,18–20,22–25,39,40 . The modest but nonsignificant mediation effect of IL‐10, which has regulatory anti‐inflammatory and B cell stimulatory activity, may reflect the dynamic nature of its secondary responses to increased proinflammatory markers 41 .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We found that IL‐6, IL‐10, and TNF‐α had a direct relationship with cognition in survivors and controls, findings that parallel prior work by others 13,18–20,22–25,39,40 . The modest but nonsignificant mediation effect of IL‐10, which has regulatory anti‐inflammatory and B cell stimulatory activity, may reflect the dynamic nature of its secondary responses to increased proinflammatory markers 41 .…”
Section: Discussionsupporting
confidence: 83%
“…We found that IL-6, IL-10, and TNF-α had a direct relationship with cognition in survivors and controls, findings that parallel prior work by others. 13,[18][19][20][22][23][24][25]39,40 The modest but nonsignificant mediation effect of IL-10, which has regulatory anti-inflammatory and B cell stimulatory activity, may reflect the dynamic nature of its secondary responses to increased proinflammatory markers. 41 IFN-γ, which is produced during immune activation and antiviral responses, and IL-8, which is a chemoattractant for neutrophils, were unrelated to cognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations